2005
DOI: 10.1111/j.1460-9568.2005.04340.x
|View full text |Cite
|
Sign up to set email alerts
|

Fyn kinase‐mediated phosphorylation of NMDA receptor NR2B subunit at Tyr1472 is essential for maintenance of neuropathic pain

Abstract: Despite abundant evidence implicating the importance of N-methyl-D-aspartate (NMDA) receptors in the spinal cord for pain transmission, the signal transduction coupled to NMDA receptor activation is largely unknown for the neuropathic pain state that lasts over periods of weeks. To address this, we prepared mice with neuropathic pain by transection of spinal nerve L5. Wild-type, NR2A-deficient, and NR2D-deficient mice developed neuropathic pain; in addition, phosphorylation of NR2B subunits of NMDA receptors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
150
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(161 citation statements)
references
References 46 publications
11
150
0
Order By: Relevance
“…We found that after peripheral nerve injury, the cells expressing p-Src, as well as p-Lck and p-Lyn, are microglia rather than neurons or astrocytes in the dorsal horn. Furthermore, a recent report showed that phosphorylation of N-methyl-Daspartate receptors by Fyn is essential for the maintenance of neuropathic pain (Abe et al, 2005). Considering that nerve injury induces a significant increase in p-Src family expression in spinal microglia, these findings suggest that other SFKs, such as Fyn or Yes, are also activated in microglia and play a role in the generation of mechanical hypersensitivity.…”
Section: Discussionmentioning
confidence: 89%
“…We found that after peripheral nerve injury, the cells expressing p-Src, as well as p-Lck and p-Lyn, are microglia rather than neurons or astrocytes in the dorsal horn. Furthermore, a recent report showed that phosphorylation of N-methyl-Daspartate receptors by Fyn is essential for the maintenance of neuropathic pain (Abe et al, 2005). Considering that nerve injury induces a significant increase in p-Src family expression in spinal microglia, these findings suggest that other SFKs, such as Fyn or Yes, are also activated in microglia and play a role in the generation of mechanical hypersensitivity.…”
Section: Discussionmentioning
confidence: 89%
“…The kinase most closely related to Src is Fyn, and PNI-induced behaviors are suppressed in Fyn null mutant mice 40 , indicating that Fyn may also be important for these behaviors. It is known that Fyn does not interact with ND2 18 and here we found that Src40-49Tat does not affect the association of Fyn with NMDARs.…”
Section: Within the Nmdar Complex Src Enhances Nmdar Function By Incmentioning
confidence: 99%
“…Src (40)(41)(42)(43)(44)(45)(46)(47)(48)(49) or sSrc (40)(41)(42)(43)(44)(45)(46)(47)(48)(49) were added to the intracellular solution for a final concentration of 0.015 mg ml −1 . Whole-cell currents were recorded with an AxoPatch 200B amplifier (Axon Instruments), digitized (20 KHz) and analyzed offline.…”
Section: Electrophysiological Recordingsmentioning
confidence: 99%
“…This ectopic activity might be driving mechanisms of central sensitization such as involving NMDA receptor phosphorylation (Abe et al, 2005;Gao et al, 2005;Ultenius et al, 2006), altered signal transduction mechanisms such as increased CaMKII activity (Dai et al, 2005), tyrosine kinases (Yang et al, 2004), a shift in the anion gradient (Coull et al, 2003;Keller et al, 2007), microglial activation (Coull et al, 2005), apoptosis (Scholz et al, 2005), decreased inhibitory mechanisms (Back et al, 2006;Idanpaan-Heikkila and Guilbaud, 1999;Kohno et al, 2005;Moore et al, 2002;Porreca et al, 1998;Scholz et al, 2005;Toda et al, 1998), and others. It is thought that this enhanced responsivity of sensory neurons in the spinal dorsal horn, termed central sensitization (Ji and Woolf, 2001;Sotgiu and Biella, 2000) or long term potentiation (Ji et al, 2003;Sandkuhler and Liu, 1998), contributes to neuropathic pain by facilitating and prolonging transmission of nociceptive information to supraspinal pain networks Sun et al, 2001).…”
Section: Contribution Of Peripheral Drive To Spontaneous Activity Of mentioning
confidence: 99%